2011
DOI: 10.1104/pp.111.182519
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thermostability of Thylakoid Membranes in Isoprene-Emitting Leaves Probed with Three Biophysical Techniques    

Abstract: Three biophysical approaches were used to get insight into increased thermostability of thylakoid membranes in isoprene-emittingplants.Arabidopsis (Arabidopsis thaliana) plants genetically modified to make isoprene and Platanus orientalis leaves, in which isoprene emission was chemically inhibited, were used. First, in the circular dichroism spectrum the transition temperature of the main band at 694 nm was higher in the presence of isoprene, indicating that the heat stability of chiral macrodomains of chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
168
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 78 publications
8
168
0
1
Order By: Relevance
“…Indeed, with circular dichroism spectroscopy, it has been shown that isoprene deficiency inhibits the formation of the chirally organized macrodomains. This effect in turn decreases the thermal stability of thylakoid membranes (Velikova et al, 2011). We also observed the significant downregulation of the cytochrome b 6 f complex in NE lines (Velikova et al, 2014), which might inhibit the production of ATP in isoprene-suppressed plants.…”
Section: Functional Changes Relate To Structural Alterations In Ne Chmentioning
confidence: 58%
See 4 more Smart Citations
“…Indeed, with circular dichroism spectroscopy, it has been shown that isoprene deficiency inhibits the formation of the chirally organized macrodomains. This effect in turn decreases the thermal stability of thylakoid membranes (Velikova et al, 2011). We also observed the significant downregulation of the cytochrome b 6 f complex in NE lines (Velikova et al, 2014), which might inhibit the production of ATP in isoprene-suppressed plants.…”
Section: Functional Changes Relate To Structural Alterations In Ne Chmentioning
confidence: 58%
“…One of the proposed biological functions of isoprene is the stabilization of thylakoid membrane structures through modification of the lipid environment and organization of the pigment-protein complexes in thylakoid membranes (Velikova et al, 2011). Indeed, several clear alterations were evident in thylakoid membrane lipids and fatty acid composition due to the translational suppression of isoprene synthase activity in poplar plants.…”
Section: Suppression Of Isoprene Biosynthesis Decreases the Chloroplamentioning
confidence: 99%
See 3 more Smart Citations